How rock glacier hydrology, deformation velocities and ground temperatures interact: Examples from the Swiss Alps. (5th September 2019) - Kenner, Robert; Pruessner, Luisa; Beutel, Jan; Limpach, Philippe; Phillips, Marcia
Abstract: An increasing number of studies highlight the controlling influence of water on rock glacier deformation velocities. The link between the concept of water‐driven shearing processes and numerous observations of correlating mean annual air or ground temperatures and rock glacier velocities is discussed here. We present a dataset measured at the Schafberg rock glacier in the Eastern Swiss Alps, complemented by temperature data from three other rock glaciers in the Swiss Alps, which allowed us to reconstruct the processes influencing both mean annual ground temperatures and rock glacier deformation velocity. Rock glacier hydrology is the parameter linking rock glacier temperature and velocities and is a crucial influencing factor. The main external forcing parameter appart from mean annual air temperature is early winter snow coverage. The study shows that the concept of water being a controlling factor for rock glacier velocity is no contradiction to the observed correlations between air or ground temperature and rock glacier deformation.